Loyalty Risk – with Special Consideration to its Evaluation and Measurement - Hap, Wiesława (Edukacja Ekonomistów i Menedżerów, 2012)
Making decisions about investments in human capital is burdened with risk. Therefore, it is necessary to master risk handling. This also applies risking the loyalty of employees in the organization. The article defines the concept of risk based on loyalty and the chosen method attempts to estimate it, indicating the instruments dealing with risk loyalty.